An economic examination of private insurance claims among adolescents and young adults who were enrolled in hospice during the last year of life - Keim-Malpass J; Cohrs AC; Lindley LC; Leslie DL (Dove Medical Press, 2018)
Jessica Keim-Malpass,1,2 Austin C Cohrs,3 Lisa C Lindley,4 Douglas L Leslie3 1Department of Acute and Specialty Care, School of Nursing, University of Virginia, Charlottesville, VA, USA; 2Department of Pediatrics, School of Medicine, University of Virginia, Charlottesville, VA, USA; 3Department of Public Health Sciences, Penn State College of Medicine, Hershey, PA, USA; 4College of Nursing, University of Tennessee-Knoxville, Knoxville, TN, USA Purpose: The purpose of this study was to generate baseline data on the health characteristics, health care utilization, and health care spending among privately insured adolescents and young adults (AYA), who were enrolled in hospice care during their last year of life. Methods: A retrospective, nonexperimental design was used to collect and analyze longitudinal claims data from the Truven Health MarketScan™ database. The sample included AYA (aged 15–24 years) who utilized hospice during their last year of life. Results: Totally, 17,408 AYA were included in this analysis. Mean hospice length of stay (LOS) was low overall, but there was a statistically significant difference in hospice LOS in ages 15–19 years (mean 3.56, SD 15.17 days) compared with those aged 20–24 years (mean 2.26, SD 8.24; P<0.001 days). More than a third (37%) of the AYAs used the emergency department during the last year of life and 83% sought care from a primary care visit. However, only 6% of the sample who were hospice enrollees used frequent inpatient hospital services. Conclusions: This study provides preliminary data for private insurance expenditures and clinical utilization for AYA who were enrolled in hospice. This analysis also provides initial evidence to suggest extremely short hospice LOS for AYAs prior to the end of life and represents an area of future research need. Keywords: adolescent, young adult, hospice, economic, private health insurance, end of life